Penanaman Nilai Karakter Disiplin Siswa Kelas X Di SMA Antartika Sidoarjo - Nur Sabilatul Ulfa; Suhari Suhari (Jurnal Kajian dan Penelitian Umum, 2023)
The Indonesian state is currently faced with destruction, especially in the world of education. The devastation is a moral crisis that occurs among students. An example of a moral crisis that often occurs among students is a brawl between students, not obeying the rules of discipline in schools. Based on several examples of this moral crisis, it can be proven that a person's behavior in being disciplined properly and correctly in the present has been greatly weakened. From the various problems that entangle the younger generation now, it needs to be minimized by the existence of character education, especially disciplinary character in order to become a person who is responsible for obeying the surrounding regulations. The purpose of this study is to examine the forms of instillation of disciplinary character values of class X students at Sidoarjo Antarctica High School as a whole and also to identify the role of teachers and parents in strengthening the cultivation of disciplinary character values of class X students at Sidoarjo Antarctic High School clearly. This study used a descriptive qualitative method to find data on the cultivation of disciplinary character values of class X students at Sidoarjo Antarctica High School and the data were taken through observations on the implementation of discipline, interviews with class x students, teachers, parents, and supporting documentation. The results of this study obtained that the cultivation of disciplinary character values of class X students at Sidoarjo Antarctic High School has been carried out well as well, arriving at school on time and wearing uniforms according to school regulations, always maintaining order. In this implementation, there is also an important role of teachers and parents who succeed in educating the character of discipline in students.